Challenges in osteochondral repair—a critical review - Jalaja Aswathy; Josna Joseph; Annie Abraham (Biofunctional Materials)
Osteochondral (OC) tissue repair is a significant challenge in managing osteoarthritis patients, as osteoarthritis (OA) progressively deteriorates both cartilage and subchondral bone, reducing quality of life. Restoring OC regions with complete structural and functional recovery is crucial. Despite availability of various OC constructs for OA joint repair, ensuring their stability and bone support remains problematic. The primary obstacle in attaining favourable patient outcome is designing constructs tailored to individual needs. This critical review addresses the various challenges in OC tissue repair, including (i) anatomical complexities, (ii) biological approaches to restoring the OC interface, and material selection, (iii) cell sources for reconstruction, and (iv) recreating a coordinated microenvironment. The findings arising out of this introspection, underscore the need for innovative strategies to overcome these OC tissue repair limitations, aiming at restoring OC unit structure and function in OA patients.